P1-S1.48 Prevalence of syphilis in antenatal clinic attenders and associated risk factors. (10th July 2011) - Adu-Sarkodie, Y; Mensah, P; Opoku, B K; Mayaud, P; Peeling, R
Abstract : Background: Maternal syphilis can adversely affect pregnancy outcomes. This can be averted if women are tested and treated adequately during pregnancy. As part of a programme towards the introduction of routine syphilis testing and treatment in pregnancy in Ghana, the prevalence of syphilis in pregnant women attending a tertiary facility (also used as primary facility by pregnant women) was carried out. Associated risk factors for syphilis seropositivity was also determined. Methods: 841 pregnant women were tested for syphilis using a Rapid Plasma Reagin kit (Immutrep Carbon Antigen, Omega Diagnostics, UK). All sero-reactive samples were confirmed with a TPHA assay (Immutrep TPHA, Omega Diagnostic, UK). A questionnaire seeking socio-demographic information, history of previous pregnancy outcomes, and history sexually transmitted infections was administered to the enrolled women. Results: 6 out of the 841 (0.71%) women were seropositive for syphilis (RPR reactive, TPHA positive), out of which one had a high RPR titre (1:8), one a RPR titre of 1:4 and four had low RPR titres of 1:2. None of the risk factors studied were associated with syphilitic infection. Conclusion: A low prevalence of maternal syphilis was found in this urban population. This is low in comparison with a national prevalence of 6.5% among pregnant women, and high prevalences in rural settings in Ghana. This may be due to a low prevalence of syphilis in this urban area or better access to STI testing and treatment in this area which the women take advantage of due to the National Health Insurance Policy. Even with this low prevalence, studies indicate that testing and treatment is still cost -effective.